Age‑dependent FRAX‑based assessment and intervention thresholds for therapeutic decision making in osteoporosis in the Malaysian population - Chellappah Thambiah, Subashini; Ratnasingam, Jeyakantha; Niyaz, Mariyam; Mariyappan, Shanmugam; Ong, Terence; Siew, Pheng Chan; Swan, Sim Yeap; Fen, Lee Hew; Lekamwasam, Sarath; Velaiutham, Shanty (Springer Nature, 2024)
Summary Fracture risk stratification is crucial in countries with limited access to bone density measurement. 24.8% women were in the high-risk category while 30.4% were in the low-risk category. In the intermediate risk group, after recalculation of fracture risk with bone density, 38.3% required treatment. In more than half, treatment decisions can be made without bone density. Purpose We aimed to examine the role of age-dependent intervention thresholds (ITs) applied to the Fracture Risk Assessment (FRAX) tool in therapeutic decision making for osteoporosis in the Malaysian population. Methods Data were collated from 1380 treatment-naïve postmenopausal women aged 40–85 years who underwent bone mineral density (BMD) measurements for clinical reasons. Age-dependent ITs, for both major osteoporotic fracture (MOF) and hip fracture (HF), were calculated considering a woman with a BMI of 25 kg/m2, aged between 40 and 85years, with a prior fragility fracture, sans other clinical risk factors. Those with fracture probabilities equal to or above upper assessment thresholds (UATs) were considered to have high fracture risk. Those below the lower assessment thresholds (LATs) were considered to have low fracture risk. Results The ITs of MOF and HF ranged from 0.7 to 18% and 0.2 to 8%, between 40 and 85years. The LATs of MOF ranged from 0.3 to 11%, while those of HF ranged from 0.1 to 5.2%. The UATs of MOF and HF were 0.8 to 21.6% and 0.2 to 9.6%, respectively. In this study, 24.8% women were in the high-risk category while 30.4% were in the low-risk category. Of the 44.8% (n=618) in the intermediate risk group, after recalculation of fracture risk with BMD input, 38.3% (237/618) were above the ITs while the rest (n=381, 61.7%) were below the ITs. Judged by the Youden Index, 11.5% MOF probability which was associated with a sensitivity of 0.62 and specificity of 0.83 and 4.0% HF probability associated with a sensitivity of 0.63 and a specificity 0.82 were found to be the most appropriate fixed ITs in this analysis. Conclusion Less than half of the study population (44.8%) required BMD for osteoporosis management when age-specific assessment thresholds were applied. Therefore, in more than half, therapeutic decisions can be made without BMD based on these assessment thresholds.